Sabemos que 2arcsinx=arcsin(2x√1−x2)arcsinx+arcsiny=arcsin[x√1−y2+y√1−x2]3arcsinx=arcsinx+2arcsinx Así x=x,y=2x√1−x2 utilizando ( 1 ), ( 2 ) y ( 3 ): 3arcsinx=arcsin[x√1−2x√1−x22+2x(1−x2)]=arcsin[x√1−4x2(1−x2)+2x(1−x2)]=arcsin[x√1−2(2x2)+(2x2)2+2x(1−x2)]=arcsin[x√(2x2−1)2+2x(1−x2)]=arcsin[x|2x2−1|+2x(1−x2)]
Si 2x2−1 es positivo, entonces |2x2−1| es 2x2−1 .
Si 2x2−1 es negativo, entonces |2x2−1| es −2x2+1 .
Gama de x es −1≤x≤1⟹0≤x2≤1⟹0≤2x2≤2 .
Para x∈(−1√2,+1√2) entonces 2x2−1 es negativo.
Para x∈(−1,−1√2)∪(+1√2 ,1) entonces 2x2−1 es positivo.
Así, para x∈(−1√2,+1√2) 3arcsinx=arcsin[x|2x2−1|+2x(1−x2)]=arcsin[−2x3+x+2x(1−x2)]=arcsin[3x−4x3] Así, para x∈(−1,−1√2)∪(+1√2,1) 3arcsinx=arcsin[x|2x2−1|+2x(1−x2)]=arcsin[2x3−x+2x−2x3]=arcsin[x] Pero claramente, 3arcsinx=arcsin[3x−4x3] .
¿Qué hay de malo en esta prueba?